(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Purulent-inflammatory lesions such as abscesses and phlegmons in the maxillofacial area represent serious clinical conditions in pediatric patients. Due to specific anatomical and immunological features in children, these infections can progress rapidly and result in life-threatening complications if not managed promptly. This research investigates optimized diagnostic and treatment approaches aimed at improving clinical outcomes for children affected by such conditions. The study also evaluates preventive measures designed to mitigate the risk of associated complications. Drawing upon clinical data, comprehensive treatment algorithms were established—integrating conservative therapy, surgical intervention, and postoperative support. The results highlight the necessity for early diagnosis, interdisciplinary cooperation, and tailored therapeutic plans to ensure optimal patient care.